IgM, IgG, and IgA influenza-specific plasma cells express divergent transcriptomes - Price, Madeline J. (J Immunol, 2019)
Antibody secreting cells (ASC) or plasma cells are essential components of the humoral immune system. While antibodies of different isotypes have distinct functions, it is not known if the ASC that secrete each isotype are also distinct. ASC downregulate their surface BCR upon differentiation, hindering analyses that couple BCR information to other molecular characteristics. Here, we developed a methodology using fixation, permeabilization, and intracellular staining coupled with cell sorting and reversal of the crosslinks to allow RNA-seq of isolated cell subsets. Using hemagglutinin (HA) and nucleoprotein (NP) antigen-specific B-cell tetramers and intracellular staining for IgM, IgG, and IgA isotypes, we were able to derive and compare the gene expression programs of ASC subsets that were responding to the same antigens following influenza infection in mice. Intriguingly, while a shared ASC signature was identified, each ASC isotype-specific population expressed distinct transcriptional programs controlling cellular homing, metabolism, and potential effector functions. Additionally, we extracted and compared BCR clonotypes and found that each ASC isotype contained a unique, clonally related CDR3 repertoire. In summary, these data reveal specific complexities in the transcriptional programming of antigen-specific ASC populations.